2022
DOI: 10.1037/men0000402
|View full text |Cite
|
Sign up to set email alerts
|

Association between psychotherapy use, sexual orientation, and traditional masculinity among psychologically distressed men.

Abstract: Heterosexual-identified men, as compared to non-heterosexual-identified men, are less likely to seek out psychotherapy when experiencing psychological distress. Stronger endorsement of traditional masculinity ideologies (TMI) has been reported to be associated with reduced psychotherapy use among men. However, the relationship between psychotherapy use, TMI, and sexual orientation needs to be explored. A total of 728 psychologically distressed men (59.9% heterosexual-identified, 40.1% non-heterosexual-identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

5
4

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 103 publications
1
26
0
Order By: Relevance
“…Regarding current psychotherapy use, students were asked directly whether they were currently receiving psychotherapy (“Yes”/“No”), while the question about intention to start psychotherapy asked students whether they had thought about receiving psychotherapy (“Yes”/“No”). In a previous study with German-speaking students, the item on current psychotherapy use showed high reliability (Cohen’s kappa κ = 0.92) over a one-month period, as well as significant convergent validity with depression symptoms (PHQ-9; point biserial correlation coefficient r pb = 0.18, p < 0.001) and anxiety symptoms (GAD-7; r pb = 0.17, p < 0.001) [ 46 ]. On the other hand, the same study supported the discriminant validity of this item with significant negative correlations between current psychotherapy use and self-esteem ( r pb = −0.19, p < 0.001), optimism ( r pb = −0.10, p = 0.009), and resilience ( r pb = −0.11, p = 0.008) [ 46 ].…”
Section: Methodsmentioning
confidence: 92%
See 1 more Smart Citation
“…Regarding current psychotherapy use, students were asked directly whether they were currently receiving psychotherapy (“Yes”/“No”), while the question about intention to start psychotherapy asked students whether they had thought about receiving psychotherapy (“Yes”/“No”). In a previous study with German-speaking students, the item on current psychotherapy use showed high reliability (Cohen’s kappa κ = 0.92) over a one-month period, as well as significant convergent validity with depression symptoms (PHQ-9; point biserial correlation coefficient r pb = 0.18, p < 0.001) and anxiety symptoms (GAD-7; r pb = 0.17, p < 0.001) [ 46 ]. On the other hand, the same study supported the discriminant validity of this item with significant negative correlations between current psychotherapy use and self-esteem ( r pb = −0.19, p < 0.001), optimism ( r pb = −0.10, p = 0.009), and resilience ( r pb = −0.11, p = 0.008) [ 46 ].…”
Section: Methodsmentioning
confidence: 92%
“…In a previous study with German-speaking students, the item on current psychotherapy use showed high reliability (Cohen’s kappa κ = 0.92) over a one-month period, as well as significant convergent validity with depression symptoms (PHQ-9; point biserial correlation coefficient r pb = 0.18, p < 0.001) and anxiety symptoms (GAD-7; r pb = 0.17, p < 0.001) [ 46 ]. On the other hand, the same study supported the discriminant validity of this item with significant negative correlations between current psychotherapy use and self-esteem ( r pb = −0.19, p < 0.001), optimism ( r pb = −0.10, p = 0.009), and resilience ( r pb = −0.11, p = 0.008) [ 46 ]. In the present study, convergent validity of the two items was further supported by a significant positive correlation between current psychotherapy use and suicidal ideation (Pearson’s phi coefficient r φ = 0.15, p < 0.001) as well as between the intention to start psychotherapy and suicidal ideation ( r φ = 0.30, p < 0.001).…”
Section: Methodsmentioning
confidence: 92%
“…First, some restraints to generalizability arise from the sample's composition, namely psychologically distressed men, men in psychotherapy, and non-heterosexual identified men being overrepresented. Because men, especially those high in TMI, are generally more reluctant to seek help (Eggenberger et al, 2021(Eggenberger et al, , 2022Walther & Seidler, 2020), the high prevalence of men using psychotherapy and being psychologically distressed in the present sample suggest a self-selection bias, as participation was based on interest in a mental health self-assessment. Similarly, the high proportion of nonheterosexual men may be explained by increased psychological burden due to the marginalization of minorities (Kelleher, 2009;King et al, 2008;Timmins et al, 2017).…”
Section: Limitations and Future Directionsmentioning
confidence: 85%
“…Thus, it is important that future treatment programs that use cognitive behavioral therapy to address ED in men (Andersson et al, 2011;McCabe, 2001;Metz et al, 2017) clarify PMB and, if necessary, disconnect or even resolve them from ED. Similar attempts already exists with regard to the treatment of major depressive disorder in men (Walther et al, 2021;Walther & Seidler, 2020) or psychotherapy uptake in general (Eggenberger et al, 2021(Eggenberger et al, , 2022. Manhood should be detached from the ability to achieve an erection through disputation of PMB and cognitive restructuring in order to relieve the affected men of the double pressure of needing to achieve an erection and to stabilize the threatened masculinity self-concept.…”
Section: Integration Of Findingsmentioning
confidence: 97%